PENGARUH NET INTEREST MARGIN DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSETS: Studi Kasus pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Budianto, Erwin; Romlah, Siti (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
This study to determine the effect and analyze of the Net Interest Margin and Non Performing Loan partial influence on Return on Assets banking companies in Indonesia Stock Exchange. The approach taken in this research is quantitative and associative approach. The population in this research are all banking go public companies listed in Indonesia Stock Exchange which amounted to 43 companies. The sample in this research is 7 companies. The independent variables used in this study are Net Interest Margin and Non Performing Loan and dependent variable is Return on Assets Data collection techniques using documentation. The method of analysis used is the normality test, the classical assumption test, simple linear regression test, hypothesis test and coefficient of determination. Data processing in this study using Software SPSS (Statistic Package for the Social Scien) 25 for window. The results show that partially, Net Interest Margin has an effect on Return on Assets. While Non Performing Loan has no effect on Return on Assets. Keywords : Net Interest Margin, Non Performing Loan, Return on Assets